Between Caatinga and Atlantic Forest: Floristic Composition in a Transition Area in Northeast Brazil - Anna Cláudia Miranda Campos; Grênivel Mota da Costa; Everton Hilo Souza; Aurélio José Antunes Carvalho; Lidyanne Yuriko Saleme Aona (Floresta e Ambiente, 2023)
Abstract The objective of this study was to carry out an inventory of the vascular plant species of Serra do Jatobá in the municipality of Milagres, Bahia. The survey included species of all habits and respective degrees of endemism, phytogeographic domains and threat categories, to contribute data about the flora of the Bahia semiarid region to enable management and preservation of species, to support the future creation of conservation units in Bahia inselbergs. We recorded 317 species, 208 genera and 71 families, with predominance of species belonging to the Bromeliaceae, Fabaceae, Euphorbiaceae and Asteraceae families. We identified 53 endemic species of the Caatinga, and 18 exclusive to the Atlantic Forest. Of these species, 24 are endemic to Bahia and five species are considered vulnerable. The floristic survey of Serra do Jatobá demonstrated high biodiversity, reinforcing the importance of ongoing research in the area for the implementation of a conservation unit.